QIBLA LASER SEBAGAI ALAT PENENTU ARAH KIBLAT MALAM HARI DENGAN MENGGUNAKAN POSISI HARIAN RASI BINTANG - Fikri Darul Falah (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2025)
The determination of the Qibla direction today commonly relies on solar-based instruments such as the theodolite, which provides high measurement accuracy. However, these tools face limitations under unfavorable weather conditions when sunlight is unavailable. This study aims to develop an alternative Qibla direction measurement method using the daily positions of star constellations with a device called the Qibla Laser. The research adopts a research and development approach, combining observation, experimentation, and evaluation, grounded in Islamic astronomy (ilmu falak). Data were collected through participatory observation and field experiments using the Qibla Laser as primary data, while secondary data were obtained from relevant literature and documents concerning raṣdu al-qiblah. A descriptive analysis was used to explain the astronomical and mathematical basis of the tool, while a comparative analysis was applied to assess its accuracy against contemporary calculations and Ephemeris data. The findings indicate two main results: first, the Qibla Laser is a viable alternative for determining the Qibla direction when solar-based tools are unusable; second, it offers high accuracy as it targets the star’s center point rather than relying on light reflection like sunlight. This innovation contributes to the advancement of practical and precise astronomical instruments for Qibla determination.